Maverick Enterprise : Anti Rust Spray / Fakhrul Azfar Ahmad Husni ...[et al.] - Ahmad Husni, Fakhrul Azfar; Kamarulzaman, Mohamad Iqbal; Mohamed Paharudin, Muhammad Taufiq; Mohamad Nayan, Nur Afiqah; Middel, Yiririachnny (2017)
As for the business, we are producing anti rust spray for Malaysian. People nowadays want something that simple, easy to use and act effectively but also at reasonable price. We made our rust remover in liquid form to reduce our cost and market price and also easy to use. We use strong alkaline powder and strong acid to maximize the effect. Through our long term research and observation, we had planned to set up this business because we can see wider prospect of this sector in the future. Apart from that, we have observed that there are a few competitors that involves in this business. So, we take these opportunities to expand our business because we are qualified with skills.